2020
DOI: 10.3390/medicina56070335
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Comparisons of Quadriceps Thickness after Anterior Cruciate Ligament Reconstruction

Abstract: Background and objectives: Anterior cruciate ligament reconstruction (ACLR) often results in quadricep atrophy. The purpose of this study was to compare the bilateral thickness of each quadricep component before and after ACLR. Materials and Methods: Cross-sectional study design. In 14 patients who underwent ACLR, bilateral quadricep muscle thicknesses were measured using a portable ultrasound device, 1 h before and 48–72 h after ACLR. Two-way analysis of variance (ANOVA) was used to compare muscle thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
(61 reference statements)
4
6
0
Order By: Relevance
“…While the VI did not show a significant difference between the two groups, the large effect size (r= 0.525) was found. A previous study reported a significant decrease in VI thickness of the reconstructed limb 2-3 days after ACLR and the muscle thickness reduction was continued until 7 days after surgery [3]. The current investigation could support the previous findings and it may influence to another functional task such as isokinetic knee extension.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…While the VI did not show a significant difference between the two groups, the large effect size (r= 0.525) was found. A previous study reported a significant decrease in VI thickness of the reconstructed limb 2-3 days after ACLR and the muscle thickness reduction was continued until 7 days after surgery [3]. The current investigation could support the previous findings and it may influence to another functional task such as isokinetic knee extension.…”
Section: Discussionsupporting
confidence: 86%
“…Several studies have reported that quadriceps muscle atrophy was prominently observed in patients who underwent ACL reconstruction [2,3,5]. The quadriceps muscle is mainly responsible for knee extension, and each muscle had a different function, so it is important to identify the atrophied muscle among the quadriceps muscles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ideally, the CSA of a muscle should be measured where the CSA is greatest to draw the best inference regarding the force that muscle can produce (25,29). Measuring the quadriceps as a group may in fact exclude a large portion of muscle CSA because the optimal thickness of each muscle is located in different regions along the thigh (5,9,11) This is important because the individual muscles that make up quadriceps group may have distinct functions over the knee joint (7,10).…”
Section: Discussionmentioning
confidence: 99%